Gendered mobilities in the making: moving from a pedestrian to vehicular mobility landscape in Shimshal, Pakistan. (4th July 2018) - Cook, Nancy; Butz, David
ABSTRACT: Although feminist geographers understand gender and mobility as mutually constitutive social processes, few studies explain how gender relations are constituted in particular mobility contexts, and how and why they shape mobility patterns in specific socio-spatial circumstances. We address these questions in an analysis of gendered mobilities in Shimshal, Pakistan, which until recently have taken shape in the context of a pedestrian mobility regime. The gender and mobility relationship has transformed as vehicular mobilities have replaced pedestrian mobilities with the construction of the Shimshal road. To demonstrate empirically the co-constitution of gender and mobility, we analyze aspects of socio-spatial context that have shaped gendered pedestrian mobilities, followed by those associated with the new vehicular mobility regime that are modifying gender relations in Shimshal. Shifting gender relations reshape corporeal mobility patterns. Road infrastructure has enhanced men's and youth's outbound travel as wage earners and students, respectively. These mobilities have reshaped women's capacity to move, constraining their mobility beyond the village. As prosperity becomes contingent on outbound movement, men's and youths' social horizons and mobilities are expanding, while women's compromised access to mobility as a social resource produces new mobility hierarchies and gendered exclusions.